The Value of 18F-FDG PET/CT and Abdominal PET/MRI as a One-Stop Protocol in Patients With Potentially Resectable Colorectal Liver Metastases - Zhou, Nina; Guo, Xiaoyi; Sun, Hongwei; Yu, Boqi; Zhu, Hua; Li, Nan; Yang, Zhi (Frontiers in Oncology, 2021)
Purpose: The aim of this study was to evaluate the clinical value of simultaneous PET/CT and abdominal PET/MRI in the detection of liver metastases and extra hepatic disease (EHD) in patients with potentially resectable colorectal liver metastases (CLM). Methods: Fifty-six patients with CLM underwent conventional imaging (chest and abdomen CT, liver CT or MRI) and PET imaging (18F-FDG PET/CT and subsequent liver PET/MRI) for staging and restaging. Diagnostic ability of PET imaging was compared with conventional imaging. Abnormal findings were correlated with follow-up imaging and/or histology. The influence of the PET imaging findings was categorized for each patient in relation to operability and other significant findings. The clinical management included three modalities (surgery for resectable CLM, unresectable CLM with conversion treatment, and systemic therapy). The clinical impact of the imaging modality was analyzed. The operative histopathological analysis and/or imaging follow-up were performed as the standard of reference. Results: This study enrolled a total of 56 patients (median age 60 years, 62.5% were male, 36 with colon cancer and 20 with rectal cancer). For EHD detection, PET/CT detected more EHD than conventional imaging (60.7% vs 46.4%). PET/CT had different findings in 19 (33.9%) patients, including downstaged in 4 (7.1%) patients and upstaged in 15 (26.8%) patients. For liver lesion detection, PET/MRI showed comparable detection ability with CE-MRI and CE-CT (99.5%, 99.4%, 86.5%, respectively) based on lesion analysis. PET imaging had major impact in 10/56 (17.9%) patients (4 from unresectable to resectable, 6 from resectable to unresectable), and minor impact in 4/56 (7.1%) patients for changing the surgery extent. The therapeutic strategies had been altered in total 14/56 patients (25%) after PET/CT /MRI scans. Conclusion: The results of this study indicate that simultaneous 18F-FDG PET/CT and abdominal PET/MRI scans can provide accurate information regarding CLM status and EHD, and can affect the management of 25% of the patients by changing the therapeutic strategies that determined by conventional imaging. This new modality may serve as a new one-stop method in patients with potentially resectable CLM.